EPİZODİK VE KRONİK MİGRENLİ OLGULARDA SEREBRAL HÜCRESEL HASARIN GÖSTERGESİ OLAN SERUM NSE VE S100B DÜZEYLERİYLE İNFLAMATUVAR NÖROPEPTİT CALSİTONİN GEN RELATED PEPTİD ARASINDAKİ İLİŞKİ - ACAR, VUSLAT (Fırat Üniveristesi, 2017)
Migren hastalığının etyopatogenezi halen tam olarak aydınlatılamamıştır. Bu konudaki en son görüş; internal veya eksternal tetikleyici bir etmenle beyinde meninkslerde sensoriyel sinir uçlarından calcitonin gen-related peptide (CGRP), substance P(SP) ve neurokinin A(NKA) gibi peptitlerin meniskler içine salınması, bunların meninkslerde nörojenik inflamasyona yol açması, bu durumun sensoriyel sinir uçlarında ağrılı impulsları doğurması, ortaya çıkan bu ağrı impulslarının trigeminal sinir aracılığı ile beyine iletilerek migren başağrısının ortaya çıkmasıdır. Bizim çalışmamızda da olgulardaki NSE ve S100B düzeyleri ile CGRP düzeyleri arasında pozitif bir ilişki olup olmadığının incelemesi amaçlandı. Bu çalışmada IHS kriterlerine göre migren tanısı almış 30 kronik migren ve 30 epizodik migren hastası, çalışmanın amacı ve uygulama yöntemleri belirtilerek çalışmaya katılmayı kabul eden 20 sağlıklı gönüllüden oluşan kontrol grubu alındı. Hastalardan ve/veya yakınlarından detaylı bir anamnez alınarak epizodik migrenli olgularda ve kronik migrenli olgularda başağrısız bir günde; Serum S100B, NSE ve CGRP ölçümü için venöz kan örneği alınarak santrifüj edildi.S100B, NSE ve CGRP kitinin temini için FÜBAP (Fırat üniversitesi Bilimsel Araştırma ve Proje Geliştirme)'tan maddi destek sağlanması talep edildi. İstatistiksel analizler için SPSS versiyon 22.0 paket programı kullanıldı. Çalışma sonuçlarımızda; istatistiksel olarak; epizodik ve kronik migren grubunda; S100B, NSE ve CGRP değerlerinde kontrol grubuna kıyasla yükseklik tespit edilmedi. Nöronal hasarın göstergesi olan NSE ile CGRP arasında anlamlı korelasyon sadece epizodik migrenlilerde interiktal dönemde tespit edilirken, hem epizodik hem kronik migren grubunda; CGRP yüksekliği ile protein S100B arasında anlamlı korelasyon bulunamadı. Bu da migren baş ağrısı patogenezinde; kan beyin bariyerinin bütünlüğünün her hastada, her ağrı periyodunda bozulmayabileceğini veya migren patofizyolojisinden sorumlu olabilecek nöroinflamasyonun ağrının varlığı ve şiddetiyle paralellik göstermeyebileceğini düşündürmektedir. Anahtar Kelimeler: Epizodik Migren, kronik migren, nöron spesifik enolaz, S100B, calsitonin gen related peptid

Etiopathogenesis of the disease of migraine is not completely known. The latest view on the subject explains the migraine as the release of peptides such as calcitonin, gen-related peptide (CGRP), substance P (SP), and neurokinin A (NKA) from sensorial nerve ends in the brain, stimulated by an internal or external factor, into the meninx, causing neurogenic inflammation in the meninx, thus creating pain impulses at sensorial nerve ends, and transmittance of these pain impulses into the brain via trigeminal nerve, causing the migraine headache. The objective of this study, conducted with a group of episodic migraine cases, is to measure serum NSE and S100B levels that are a precise indicator of cellular damage in the brain, and serum levels of calcitonin gen-related peptide (CGRP) that causes meningeal neurogenic inflammation, which is a significant concept of the process that results in headache attacks during the period without headache, and also to measure the above mentioned parameters in a group of chronic migraine patients during the period without headache. This study included 30 patients with chronic migraine and 30 patients with episodic migraine were diagnosed with migraine according to the IHS criteria and agreed to participate in the study after being informed about the study objectives and implementation methods; and a control group composed of 20 healthy volunteers who agreed to participate in the study after being informed about the study objectives and implementation methods. The control group who consisted of 20 healthy volunteers were chosen so as to be compliant with the patients with migraine in terms of age and gender.After a detailed anamnesis was taken from the patients and/or their relatives, veneous blood sample would be taken from episodic migraine cases and from chronic migraine cases in a day without headache for serum S100B, NSE and CGRP measurements. The blood samples would be left for coagulation and would be obtained. To acquire S100B, NSE, and CGRP kit funding would be requested from Fırat University Scientific Research and Project Development department (FUBAP). SPSS version 22.0 software package would be used for statistical analyses. Data that would be collected in the study would be presented as mean ± standard deviation. The study concluded that S100B, NSE and CGRP scores of the episodic and chronic migraine group were found to be not statistically higher than those of the control group. The researchers observed a significant correlation between the NSE and the CGRP only in the patients with episodic migraine who were in the interictal phase of their diseases, while they could not observe a significant correlation between the mediator CGRP level and neurogenic inflammation of both episodic and chronic migraine groups, and protein S100B, an indicator of glial cell injury, which gave rise to thought that in the migraine headache pathogenesis, the integrity of blood-brain barrier may not be impaired in each patient. Keywords: episodic migraine, chronic migraine, neuron-specific enolase, S100B, calsitonin gen related peptid
The relationship between serum NSE and s100b levels which is the indicator of cellular demage and calsitonin gen related peptid in episodic and chronic migrain cases
Keywords: Nöroloji